siRNA Targeted to p53 Attenuates Ischemic and Cisplatin-Induced Acute Kidney Injury - Molitoris, Bruce A. (American Society of Nephrology, 2009)
Proximal tubule cells (PTCs), which are the primary site of kidney injury associated with ischemia or nephrotoxicity, are the site of oligonucleotide reabsorption within the kidney. We exploited this property to test the efficacy of siRNA targeted to p53, a pivotal protein in the apoptotic pathway, to prevent kidney injury. Naked synthetic siRNA to p53 injected intravenously 4 h after ischemic injury maximally protected both PTCs and kidney function. PTCs were the primary site for siRNA uptake within the kidney and body. Following glomerular filtration, endocytic uptake of Cy3-siRNA by PTCs was rapid and extensive, and significantly reduced ischemia-induced p53 upregulation. The duration of the siRNA effect in PTCs was 24 to 48 h, determined by levels of p53 mRNA and protein expression. Both Cy3 fluorescence and in situ hybridization of siRNA corroborated a short t½ for siRNA. The extent of renoprotection, decrease in cellular p53 and attenuation of p53-mediated apoptosis by siRNA were dose- and time-dependent. Analysis of renal histology and apoptosis revealed improved injury scores in both cortical and corticomedullary regions. siRNA to p53 was also effective in a model of cisplatin-induced kidney injury. Taken together, these data indicate that rapid delivery of siRNA to proximal tubule cells follows intravenous administration. Targeting siRNA to p53 leads to a dose-dependent attenuation of apoptotic signaling, suggesting potential therapeutic benefit for ischemic and nephrotoxic kidney injury.